1995
DOI: 10.4065/70.7.662
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Cough Associated With Subacute Bacterial Endocarditis

Abstract: Although the literature on subacute bacterial endocarditis from both the preantibiotic and antibiotic eras mentions cough as a symptom, neither bacteremia nor endocarditis is listed in reviews on chronic cough. Herein we describe a 74-year-old man who underwent an extensive workup as an outpatient because of chronic cough of 7 months' duration. Chest roentgenography, chest and sinus computed tomography, fiberoptic bronchoscopy, gallium scan, transthoracic echocardiography, and other studies revealed no apparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…" Treatment of chronic cough due to active Tb: Use additional central cough suppressants " Grade: weak ñ " Evidence: none " Chronic cough due to heart diseases: Aside from chronic left heart failure (cough generally occurs upon physical exertion or prone position), cardiac drugs including ACE inhibitors, beta-blockers (only in patients with BHR), Amiodarone (eliciting Alveolitis), AVblock II -III, endocarditis [41] and cardiac arrhythmia [42,43] can cause chronic cough. " Diffuse parenchymatous lung diseases (DPLD) -Systemic diseases with diffuse lung involvement: -DPLD: In addition to dyspnea, dry cough is the most common symptom.…”
Section: Recommendation: R21mentioning
confidence: 99%
“…" Treatment of chronic cough due to active Tb: Use additional central cough suppressants " Grade: weak ñ " Evidence: none " Chronic cough due to heart diseases: Aside from chronic left heart failure (cough generally occurs upon physical exertion or prone position), cardiac drugs including ACE inhibitors, beta-blockers (only in patients with BHR), Amiodarone (eliciting Alveolitis), AVblock II -III, endocarditis [41] and cardiac arrhythmia [42,43] can cause chronic cough. " Diffuse parenchymatous lung diseases (DPLD) -Systemic diseases with diffuse lung involvement: -DPLD: In addition to dyspnea, dry cough is the most common symptom.…”
Section: Recommendation: R21mentioning
confidence: 99%
“…verschlimmern. Herzrhythmusstörungen wurden neben Hervorrufen von akutem Husten (Kapitel 5.11) auch als Ursache des chronischen Hustens beschrieben [170 -172], Endokarditis kann ebenfalls Husten verursachen [173]. An Gefäßanomalien ist ebenfalls zu denken.…”
Section: Kardiale Ursachen Für Den Chronischen Hustenunclassified
“…Only 10 cases are reported in the literature [5][6][7][8][9][10][11][12][13][14]. It is reported that S. constellatus is not readily associated with the heart valves, which may explain why S. constellatus rarely causes IE [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…However, 1 group of S. viridans, the S. milleri group, which includes S. constellatus, S. anginosus, and S. intermedius, rarely cause IE; among these, S. anginosus is predominant [4]. S. constellatus is a very rare pathogen of IE; there are only 10 case reports in the literature [5][6][7][8][9][10][11][12][13][14]. The clinical features of IE due to S. constellatus remain unclear.…”
Section: Introductionmentioning
confidence: 99%